A Kaleidoscope of Questions: Reimagining Timed Remote Exams - Dueck, Timothy (Canadian Perspectives on Academic Integrity, 2023)
This presentation provides an overview of an innovative approach to deterring student academic misconduct when writing online tests and exams. Traditional exams which contain uniformly identical questions are swapped for multiple case study scenarios that are distributed randomly among students. Additionally, individual students are provided one of several course-based theories to apply to their given scenarios, and thus their tests and exams are comprised of question combinations that are unique to each student. There is then no utility in students trying to compare answers with each other, as the likelihood of them having the exact same question combination is remote. The move to a random case study / theory combo still achieves many course objectives, as critical thinking and understanding of core concepts is measured in the context of praxis instead of memorization. Presentation discussion includes benefits and limitations of this test / exam redesign, relative to course content and context. Attendees are invited to consider how moving to tests based on case studies can measure student learning in a way that mitigates the potential for academic misconduct through peer or textbook consultation during remote online timed examination.